2021
DOI: 10.1002/jmv.27383
|View full text |Cite
|
Sign up to set email alerts
|

Transplacental transfer of RSV antibody in Australian First Nations infants

Abstract: Respiratory syncytial virus (RSV) is the leading cause of acute lower respiratory infection hospitalisations in Aboriginal infants specifically those aged <6 months.Maternally derived RSV antibody (Ab) can protect against severe RSV disease in infancy. However, the efficiency of transplacental transfer of maternal anti-RSV Ab remains unknown in Aboriginal infants. We characterised RSV Ab in Australian First Nations mother-infant pairs (n = 78). We investigated impact of covariates including low birthweight, ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Previous studies have shown that transplacental transfer of RSV-specific antibody to the infant is usually efficient with a cord blood to maternal blood antibody titre ratio of ≥ 1 [14][15][16] . This is because IgG antibody is actively transported across the syncytiotrophoblast cells rather than a passive diffusion process which is why transplacental transfer is expected be more than one 17 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that transplacental transfer of RSV-specific antibody to the infant is usually efficient with a cord blood to maternal blood antibody titre ratio of ≥ 1 [14][15][16] . This is because IgG antibody is actively transported across the syncytiotrophoblast cells rather than a passive diffusion process which is why transplacental transfer is expected be more than one 17 .…”
Section: Introductionmentioning
confidence: 99%
“…This is because IgG antibody is actively transported across the syncytiotrophoblast cells rather than a passive diffusion process which is why transplacental transfer is expected be more than one 17 . Transplacental transfer efficiency has been defined as either normal or impaired in other studies 16,18 . Where the cord to maternal titre ratio (CMTR) is one or greater than one, this is considered as a normal or efficient transfer, while a CMTR of less than one is considered as an impaired transfer 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation